The turn of 1918 and 1919 in Lithuania in the light of unknown documents - Gierowska-Kałłaur, Joanna (Studia z Dziejów Rosji i Europy Środkowo-Wschodniej, 2020)
Dzięki nieznanym dotąd, unikalnym dokumentom odnalezionym w dwóch moskiewskich archiwach (Архив внешней политики Российской империи; Российский государственный военный архив), pisanym na przełomie 1918 i 1919 roku przez przedstawicieli dwóch stron polsko-sowieckiego frontu autorka omawia sytuację w Wilnie na przełomie grudnia 1918 i stycznia 1919 roku. Thanks to previously unknown documents found in two Moscow archives (Archive of the Foreign Policy of Imperial Russia and Russian State Military Archive), written at the turn of 1918 and 1919 by representatives of two sides of the Polish-Soviet front, the author discusses the situation in Vilnius at the turn of December 1918 and January 1919.